(untitled) (Research, Society and Development, 2025)
Companies operating in the beverage distribution sector often need their truck fleet to be available at any moment for product deliveries. However, at a particular company in this sector, a considerable number of trucks were observed sitting idle in the yard due to poor organization and execution of preventive maintenance, as well as corrective maintenance tasks that had no defined resolution timeline.The objective of this study was to propose a restructuring of the maintenance plan for a beverage distributor located in Governador Valadares, Minas Gerais. The methodology used was a case study through document analysis of direct sources such as spreadsheets and work orders. The number of trucks required per day by the company was also determined, as well as how many could be taken out of operation for maintenance. As a result, it was possible to establish a more efficient maintenance management system that adhered to scheduled deadlines. There was a significant reduction in the number of unexpected truck breakdowns, which increased the operational availability of the fleet. In addition, a considerable decrease in corrective maintenance costs was observed, resulting in greater predictability and control over the department’s resources. In conclusion, the restructuring of the maintenance plan proved essential to ensure fleet availability, logistical efficiency, and operational safety for the distributor. The adoption of systematic preventive maintenance practices not only reduced costs and unexpected failures but also contributed to improved driver satisfaction and the ability to meet delivery deadlines for customers.